Numerical Simulation and Experimental Study on the Interface Bonding of Stainless Steel Clad Plate - Jin, H.R.; Zhang, L.; Dai, C.; Yi, Y.L. (Проблемы прочности, 2018)
The rolling temperature and rate of thickness reduction directly affect the interface bonding quality, mechanical properties and microstructure of stainless steel clad plate. In order to obtain reasonable rolling process parameters, the multi-pass rolling processes of Q345R/316L stainless steel clad plate were simulated by the DEFORM software package. The distributions of stress, strain, and microstructure fields of the clad plate at different rolling temperatures and reduction rates were investigated. The bonding state of the interface was determined and the change rules governing the grain size of the rolled substrate layer also were analyzed. Vacuum hot-rolling tests were carried out to characterize the microstructure and mechanical properties. It was found that the higher the rolling temperature, the lower was the reduction rate needed to realize the interface bonding. However, too high temperatures produce a higher fraction of coarse grains, which affects the overall mechanical properties of the clad plate. It was concluded from the tests and numerical results that rolling temperature of 1150°C and reduction rate exceeding 50%, stainless allow one to produce steel clad plates with high interface bonding quality and excellent microstructure.